Entrepreneurship Role in the System of State Sport in Russia - A. A. Sergeev (Вестник Российского экономического университета имени Г. В. Плеханова, 2020)
The current state policy of Russia orients to the support of entrepreneurial activity and involvement of the population into regular physical training and playing sports. Integration of entrepreneurship in the system of state sports can provide a higher level of practical use of available market tools in budget sport organizations. Collaboration of state sport organizations and entrepreneurs in the field of sports could promote sustainable development of sport economy, raise efficiency of sport goods sales and services and intensify the search for practical combinations aimed at gaining profits in the process of everyday sport activity. State sport in Russia needs mechanisms of developing private entrepreneurial initiative. The author gives recommendations for upgrading organizational mechanisms of interaction between the state sector and private business structures and their realization can raise sport economy to a new level. Improving the level of entrepreneurial culture in the sports field in line with the growth in economic and sport results in state sport organizations is relevant to the acute goals identified in the Federal projects ‘Entrepreneurship Popularization’ and ‘Sport is a Norm of Life’, which are included in the national projects ‘Small and Medium Business and Support of Individual Entrepreneurial Initiative’ and ‘Demography’.